The study of Calotropis Gigantea leaf metabolites from Ie Brouk geothermal area Lamteuba-Aceh Besar using molecular docking. Issue 1 (February 2021) - Idroes, G M; Tallei, T E; Idroes, R; Muslem; Riza, M; Suhendrayatna
Abstract: Analysis of Analysis of the metabolite contents of C. gigantea leaf from the Ie Brouk geothermal area has been done. The metabolites were determined by Gas Chromatography Mass Spectrometry and proteins from Main Protease (6LU7) and Spike Glycoprotein (6VXX) was studied by molecular docking. The leaf sample was prepared by extraction procedure using 96% ethanol solvent. The yield obtained was analyzed by using Gas Chromatography Mass Spectrometry. Molecular docking between metabolite and proteins showed strong interactions from Urs-12-en-24-oic acid 3-oxo methyl ester, Lupenyl Acetate, Beta Amyrenyl Acetate with high binding affinity of -15.1, -14.3, and -14.1 kcal/mole to 6VXX, and -12.3, -11.1, and -11.6 kcal/mole to 6LU7, respectively. The visualization of the interaction between metabolite to an amino acid proteins showed well pocket number. The pocket number in 6LU7 were higher than 6VXX, which was contributed from a compact state structure of 6VXX. The results showed that the ethanol extract of C. gigantea from the Ie Brouk geothermal area has an enormous potential to be further developed.